Letter from Henry Isaacs to James Curtis Booth - Isaacs, Henry (1862)
Henry Issacs writes to James Curtis Booth (1810-1888) with a plea to be reinstated at the Mint. Isaacs was discharged due to his absense from work, but assures Booth that "I had been sick for some days previous... but on the day alluded to I was not able to continue." Booth notes that he has shown the letter to the Mint's Director.
Keywords: Booth, James Curtis, 1810-1888; United States Mint; Mint of the United States